Tsidy, Repahaka sy Fotsife: 15 years research on nocturnal lemurs in the Ankarafantsika National Park, Madagascar - Marine Joly (Revue de Primatologie)
Tsidy, Repahaka sy Fotsife from the Malagasy: Mouse lemur, sportive lemur and woolly lemur. "The Ankarafantsika Lemur Project", is based at the field station of Ampijoroa in the National Park of Ankarafantsika in the North-West of Madagascar and is conducted by the Institute of Zoology from the University of Veterinary Medicine Hanover (Germany) in close collaboration with the local universities of Antananarivo, of Mahajanga and Madagascar National Parks (authorities for the management of protected areas in Madagascar). The project started in 1996. The goal is to enhance our knowledge on the adaptation and evolution of a previously neglected group of primates, the nocturnal lemurs, and to contribute to their conservation. Thus, researchers study the diversity, ecology, communication and socio-biology of the nocturnal lemurs. They discovered one new mouse lemur species (Microcebus ravelobensis) in this area. They characterised aspects of the morphometry, genetics, communication, ecology, social traits and recently, cognitive abilities of sympatrically living mouse-sized (Microcebus murinus and M. ravelobensis) and cat-sized lemur species (Lepilemur edwardsi and Avahi occidentalis). Some major results are presented in this article showing the importance of exchanging experience, educating Malagasy students and field guides and joint work with Malagasy partners in order to deepen our knowledge on the biology of endemic species. This knowledge is crucial to establish efficient management plans and thus contribute to the conservation of threatened species.